Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamanetworkopen.2022.33088
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Phthalate Metabolites With Sex Hormones, Obesity, and Metabolic Syndrome in US Women

Abstract: ImportanceObesity and metabolic syndrome are highly prevalent among the US population and are associated with the dysregulation of sex hormones. An increase in obesity and metabolic syndrome may also be associated with exposure to phthalates. The association of exposure to phthalate metabolites with sex hormones and metabolic health has been understudied in the female population.ObjectiveTo evaluate the association between exposure to common phthalate metabolites with total testosterone (TT) levels, sex hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…8,10,37 In addition, reduction of environmental exposure is also useful for minimizing risk of menstrual disorders and CVD events. 3,38 A higher prevalence of HMB has been reported in women with congenital cardiovascular events. 39,40 In our study, the association remained consistent between HMB and CVD outcomes even after excluding congenital cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,37 In addition, reduction of environmental exposure is also useful for minimizing risk of menstrual disorders and CVD events. 3,38 A higher prevalence of HMB has been reported in women with congenital cardiovascular events. 39,40 In our study, the association remained consistent between HMB and CVD outcomes even after excluding congenital cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The population was divided into three subgroups based on body mass index (BMI): BMI of less than 25 were 'Normal weight', between 25 and 30 were 'Overweight', greater than or equal to 30 were defined as 'Obese'. PAEs metabolite levels were derived from urine samples, to control for the interference of renal metabolic differences in different individuals in the study, urinary creatinine levels were adjusted to accommodate variations in urine dilution (36,38,39), and the timing of blood sample collection was regulated to address diurnal fluctuations in sex hormone concentrations (36). For continuous variables, skewness and kurtosis tests were used to test whether the distribution of the data was approximately normal, and non-normal continuous variables were described using the median (IQR).…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive toxicity of PAEs, as confirmed by numerous existing studies, encompasses adverse effects on the HPG axis, including abnormal release of gonadotropin-releasing hormone and gonadotropins, along with dysfunction of sex hormone receptors and steroid hormone synthesis (23). These factors collectively contribute to a heightened prevalence of metabolic disorders (38,51). Additionally, some researchers contend that obesity, on the contrary, heightens the risk of sex hormone imbalances (52).…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates are esters of phthalic acid (1,2-benzene dicarboxylic acid) used to produce polyvinyl chloride (PVC). Epidemiological studies have identified phthalates as key culprits of suppressed reproductive hormones, altered thyroid function, and the development of obesity and metabolic syndrome [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Exposure of human corneal endothelial cells (B4G12 cell line) to phthalates increased the production of IL-1β, IL-6, and IL-8, manifesting as decreased cell proliferation and subsequent cell toxicity [ 69 ].…”
Section: Proposed Mechanisms Of Tissue and Cell Damagementioning
confidence: 99%